Teste de Apresentação da Prótese (TAP): avaliação de um novo teste para triagem de comprometimento cognitivo em usuários de próteses totais - Oliveira, Talitha Marica Cabral (2021)
During the 2019 General Session of The International Association for Dental Research (IADR), Srinivasan et al. suggested a new screening test for cognitive impairment in elderly people rehabilitated with a prosthesis. The Test entitled ‘Prosthesis Presentation Test [PPT]’ the expected action was that the participants correct the orientation of the prostheses and insert them correctly. However, the authors suggested that other studies and protocols be adapted and carried out to explore the objectives of this test. Aim: To establish a protocol for the performance of the Prosthesis Presentation Test in Portuguese “Teste de Apresentação da Prótese” (TAP) and its applicability in the elderly population and test the correlation between the TAP and sociodemographic variables, measures of cognitive function and disability. Methods: This is a cross-sectional observational study with participants using Conventional dentures who underwent a new test (TAP) in 4 different presentations to assess their cognitive performance. Correlations were calculated between the sums of the TAP scores and the independent variables, these being Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) and Cognition (Mini-Mental and Mini-Cog) through the correlation coefficient Spearman and p-value, a generalized linear model was also used Results: The sample consisted of 57 (63.3%) females and 33 (36.7%) males. The mean age was 66.7 (SD = 8.1). Regarding the assessment of Cognition by the Mini-Cog, it identified 53 (58.9%) participants with a negative assessment. For evaluation in relation to the MMSE, 69 participants (76.7%) presented mild impairment, and 21 (23.3%) presented moderate impairment and none presented severe impairment. For the independence measures, the ADL showed that 64.4% of the sample is independent, compared to the IADL 41.1% of the sample is independent. Spearman's correlation coefficient showed that Mini-cog (p = 0.003) and MMSE (p = 0.019) and IADL scores (p = 0.003) were correlated with age. There was also a strong correlation between Age and PPT inboth the position of the prosthesis and the arch (p = 0.004) and (p = 0.031) and of the IADL in relation to PPT / Position (p = 0.044). The generalized linear model showed that the increase in TAP scores was associated with increasing age and a reduction in the chance of a better TAP score was inversely associated with the number of tests performed. Conclusions:Have a strong association between TAP and age and IADL score. Increased TAP scores were associated with increasing age. TAP is an easy-to-perform test that is applicable in clinical routine.